Efecto del anillado en palto (Persea americana Mill.) cv. HASS EN EL VALLE DE CHAO, LA LIBERTAD - Vásquez Jara, Nathaly (2011)
This work was conducted from August 2009 through July 30, 2010 in Block B002. B. Module Avo in the estate of Peru SAC, located on the Panamericana Norte Km 494 in the Chao Valley Viru, La Libertad, Perú.El test objective was to evaluate the effect of banding in avocado (Persea americana Mill) cultivar Hass in different months year under the conditions of the orchards of Peru SAC Avo. in the valley of Chao, Viru district, La Libertad on the fruit set, fruit size and yield, respectively._x000D_ The first ring was made in August, the second in November, the third in January and the fourth in February. The first three treatments had 10 floors and the last 20 in each plant a branch and another ring was chosen as testigo.Los results for number of fruit set, number of fruits at harvest and yield statistically indicate the absence of statistical differences significant at 0.05 between banded and unbanded branches in any of the dates, nor among different dates anillado. En contrast, the average fruit weight was observed significant differences in the banding effect made the 23 November, 2009 and the 19 February, 2010, reducing the average weight of fruit in the ringed branch in November, on the contrary increased ringed febrero. Los August and January increased between 10-13%, the number of fruits of size 14 to 18 in banding change did not mean any change in November and February last girdling decreased by 5%.